Public Satisfaction in the Management and Use of Green Open Space in Manado City, North Sulawesi Province - Kolondam, Helly F.; Londa, Very Y.; Mambo, Rully (Journal La Bisecoman, 2024)
The community has the right to utilize public open spaces. Therefore, the government has the responsibility to provide public open spaces and provide supporting facilities that can be used by the community according to their designation. Manado City in implementing Law Number 26 of 2007 has provided public open spaces for the community. The availability of public open spaces has been utilized by the community for sports activities, recreation or simply interacting with others. The open spaces that are often used by the people of Manado City besides the Blessing Park and the coastal reclamation park are also the Sparta Tikala Field, the Wenang National Unity Park, and the KONI Sario Field. However, in its management and utilization, several complaints are still found from the community. This study was conducted to identify and analyze community satisfaction in the management and use of green open spaces in Manado City. The research design used is qualitative with a descriptive approach. Data were obtained by conducting interviews with the community who use green open spaces and the managers of green open spaces. Observations were made by visiting the existing green open spaces directly and observing all the facilities available and the activities carried out by the community when they were in the green open space. Secondary data collection was conducted by utilizing Google Scholar and ResearchGate to obtain references that can support the achievement of research objectives. Data analysis was conducted using the stages of data reduction,